Archaeology after interpretation : returning materials to archaeological theory - Alberti, Benjamin, 1968-; Jones, Andrew, 1967-; Pollard, Joshua (Walnut Creek, California : Left Coast Press, Inc., 2013)
"A new generation of archaeologists has thrown down a challenge to post-processual theory, arguing that characterizing material symbols as arbitrary overlooks the material character and significance of artifacts. This volume showcases the significant departure from previous symbolic approaches that is underway in the discipline. It brings together key scholars advancing a variety of cutting edge approaches, each emphasizing an understanding of artifacts and materials not in terms of symbols but relationally, as a set of associations that compose people's understanding of the world. Authors draw on a diversity of intellectual sources and case studies, paving a dynamic road ahead for archaeology as a discipline and theoretical approaches to material culture"--
Machine generated contents note: INTRODUCTIONIntroduction : Archaeology after Interpretation - Andrew Meirion Jones and Benjamin Alberti(with contributions from Chris Fowler, Gavin Lucas, and Joshua Pollard)PART I Relational Ontologies - Benjamin AlbertiChapter 1 - Archaeology and ontologies of scale: the case of miniaturization in first millennium northwest Argentina - Benjamin AlbertiChapter 2 - Transmorphic Being, Corresponding Affect: An Ontological Safari in South-Central California - David RobinsonChapter 3 - Carnival times and the semiopraxis of the snake: Mining and politics of knowledge- Alejandro HaberChapter 4 - Unstable contexts: re-materialising the archaeological record of domestic settings in Andean Northwest Argentina Andre;s Gustavo LaguensPART II Working with Material - Andrew Meirion JonesChapter 5 - Deception and (mis)representation: Skeuomorphs, materials and form - Chantel ConnellerChapter 6 - Archaeological Complexity: Materials, Multiplicity and the transitions to agriculture in Britain - Andrew Meirion Jones and Emilie SibbessonChapter 7 - Material worlds: a contextual archaeology of dependent architecture - Lesley McFadyenChapter 8 - Object Agency and the Katsina cult- William WalkerPART III Assembling the Social- Joshua PollardChapter 9 - What Monuments Do: Construction, Effects and Ontologies - Joshua PollardChapter 10 - Fields of Movement in the Ancient Woodlands of North America- Sarah E. Baires, Amanda J. Butler, B. Jacob Skousen, and Timothy R. PauketatChapter 11 - Is the social unstable? Implicating artefacts in the study of continuity and change: A case study from Anglo-Norman Southampton - Ben JervisChapter 12 - Assemblages, change and the duration of relations: lessons from engaging with Early Bronze Age mortuary practices in Northeast England - Chris FowlerChapter 13 - Archaeology of Placemaking and the Assembly of Monumental Worlds - Marcus BrittainPART IV Beyond Representation- Andrew Meirion JonesChapter 14 - Representational approaches to Irish passage tombs: legacies, burdens, opportunitiesAndrew CochraneChapter 15 - Material articulations of the middle-ground. The Hybridity of South Scandinavian 'Petroglyphing'- Fredrik FahlanderChapter 16 - Materials of affect: miniatures in the Scandinavian Late Iron Age (550-1050 AD) -Ing-Marie Back DanielssonChapter 17 - Archaeological visualisation and the state of disciplinary theory - Sara PerryAFTERWORDChapter 18- Discussion - Gavin LucasIndexAbout the Authors.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2014. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Archaeology -- Methodology; Antiquities -- Analysis; Electronic books